Serum Macrophage Migration Inhibitory Factor Levels in Patients with Ischemic Stroke in Iraqi Populations (Medico Legal Update, 2020)
Background: Stroke is one of the leading causes of permanent disability worldwide. The most commoncause of stroke is the occlusion of blood circulation by a thrombus (or embolism) although it can also beproduced by the rupture of a vessel and subsequent bleeding in a certain region of the brain. Strokes can,therefore, be classified as ischemic or hemorrhagic.Aim: The present study was conducted to investigate whether serum MIF levels are associated with severityin patients with ischemic stroke.Method: A total of 40 patients with ischemic stroke were included in the study who were admitted tohospital from the period between March to August 2019, and other groups consist of 40 apparently healthyindividuals. Two blood sample were taken from each patients one during attack (within 24 hours) and theother sample during follow up (within 1-3 months) for serum concentration of MIF by ELISA technique.Results: Mean serum concentration of MIF in Ischemic stroke during attack (within 24 hours) wassignificantly higher than that of Ischemic stroke during follow up (within 1-3 months) and healthy controlgroup; 17.094±2.25ng/ml versus 12.83± 4.16ng/ml and 6.407± 3.33ng/ml respectively.